Cars and consumption. (October 2013) - Newman, Daniel
Cars are increasingly accepted as a socio-environmental problem. However, they are rarely considered as a political problem. This article critiques the dominant trend for research into supposedly more sustainable alternatives to the present car system, such as electric vehicles, taking to task the major theoretical school that attempts to lead this charge. In so doing, it recognises car ownership of any variety as embroiled in the culture of consumption, and suggests that any attempt to overcome the trouble with cars will also require a fundamental reappraisal of our consumption patterns.